Peculiarities of interpersonal relationships with students in the process of distance learning - Adeishvili, Tamar (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
In the modern psychological literature, interpersonal relationships are considered as the most effective means of communication that creates a necessary condition for the development of each student. However, at the current stage, when the global pandemic swept through, the healthcare organization imposed certain restrictions and regulations, including the need to move to distance learning, which had some impact on student interpersonal relationships. Based on the above, the aim of the study was to empirically study interpersonal relationships in the distance learning process in student groups. We selected the Timothy Lear Interpersonal Relationship Test to identify the form of relationship in student groups. A total of 160 students were interviewed, including 80 first- and second-year students, and 80 third- and fourth-year students.High scores with freshmen and sophomores were revealed on the scale of attitude, obedience and cooperation. Which indicates that on the one hand they have a need to get help from those around them, to earn the trust, as well as to gain recognition. A low rate was found on the aggression scale. In the third-fourth year students, the first place is occupied by authoritarian relations, while the second place is occupied by high responsibility and generosity, or expressive willingness to help others. In the last place is a form of relationship such as indicators of subordination (moderate, shy) and aggression. In conclusion, we can say that different forms of relationships have been identified between first- and second-year students and third- and fourth-year students, which may be the result of some distance learning.